Crimes of the Franco regime, lawand transitional justice - López-López, Pedro (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The persistence of the victims of the Franco regime and their mobilization for the recovery of historical memory have achieved to rescue from oblivion the crimes of that regime, a forgetting planned by political elites in the Transition. Thanks to their struggle, these crimes have attracted the attention of the United Nations and the Argentine Justice, attention that have not obtained in the institutions of Spain. The objectives of the memorial movement are repair the dignity of the victims by the State, recognizing the rights of victims, put an end to impunity for the crimes of the dictatorship and restore the memory of the Second Republic and the Constitution of 1931.